Providing Humans With Practical, Best Practice Handling Guidelines During Human-Cat Interactions Increases Cats' Affiliative Behaviour and Reduces Aggression and Signs of Conflict - Haywood, Camilla; Ripari, Lucia; Puzzo, Jo; Foreman-Worsley, Rachel; Finka, Lauren R. (Frontiers in Veterinary Science, 2021)
The importance of animals’ experiences and associated comfort during Human-Animal Interactions (HAI), and particularly Animal Assisted Interventions (AAI), are increasingly recognised. However, there remains a paucity of published research, particularly concerning less formal but frequent HAIs to which companion animals are typically exposed, such as stroking or petting. Additionally, few practical evidence-based guides to facilitate humans’ optimal animal handling and interaction in these contexts exist. A simple set of Human-Cat Interaction (HCI) guidelines were therefore created, with the aim to enhance domestic cats’ comfort during generic HCI contexts. Based around a ‘CAT’ acronym, guidelines focused on providing the cat with choice and control (‘C’), paying attention (‘A’) to the cats’ behaviour and body language and limiting touch (‘T’), primarily to their temporal regions. Guidelines were presented to human participants during a brief training intervention, and guideline efficacy was subsequently assessed. Domestic cats available for rehoming at Battersea Dogs and Cats Home, UK (n=100) were filmed during interactions with novel members of the public (n=120). Cats were exposed to a maximum of six, five-minute interaction sessions, balanced across ‘control’ (interactions with humans pre-training) and ‘intervention’ conditions (interactions with humans post-training). For each observation, cat behaviour and posture were coded and humans’ cat-directed behaviour rated on the degree to which it reflected best practice principles. Data were extracted from a total of 535 observations and average human interaction ratings and cat behaviour values compared between control and intervention conditions via paired Wilcoxon tests. Compared to the control, humans’ interaction styles were rated as significantly more closely aligned with best-practice principles in the intervention condition. Cats also displayed significantly greater frequencies and/or durations of affiliative and positively-valenced behaviours in the intervention. In contrast, cats in the control displayed significantly greater frequencies of human-directed aggression, in addition to greater frequencies and/or durations of behaviours associated with conflict and negative valence. Results demonstrate the positive impact of practical interaction guidelines on cats’ social behaviour and comfort during HCI, with the potential to improve cats’ general experiences during interactions, reduce human-directed aggression and ultimately improve cat-human relationships.